IMPLEMENTASI PROGRAM PERGURUAN TINGGI MANDIRI GOTONG ROYONG MEMBANGUN DESA (PTMGRMD) LLDIKTI IV JAWA BARAT DAN BANTEN DESA CIPICUNG KECAMATAN CIKEDAL KABUPATEN PANDEGLANG - Sudaryono, Sudaryono; Santoso, Sugeng; Rachman, Wildan Adli; Zai, Kristeven Oktober; Oktaviano, Yoffy Gilang; Sinaga, Rivaldy Ansyah; Wildan, M.; Simbolon, Silviana (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Students from various study programs carried out Thematic Real Work Lectures (KKN) in Cipicung Village, Pandeglang Regency, from September 4 to December 24, 2024, as part of the implementation of the Tri Dharma of Higher Education in community service. This activity aims to provide a direct learning experience to students to identify, formulate, and provide solutions to community problems. The work programs carried out are prepared based on the needs of the community, including One Village One Product (OVOP), administrative governance, digitization of Islamic boarding schools, MSMEs, counseling on the dangers of drugs and online gambling, community innovation, counseling on stop bullying and increasing learning motivation, improving village offices, and making road signs and village offices. The implementation of the program is carried out through coordination with the village government, community leaders, and other community elements to ensure continued success and positive impact. As a result, this activity not only contributes to the empowerment of the Cipicung Village community, but also provides real experience for students in playing an active role in village development.